Paradoks Hukum Keadaan Darurat dalam Pasal 12 UUD 1945: Menghindari State of Exception yang Permanen dalam Sistem Hukum Tata Negara Indonesia - Sudirman Sudirman; Fathul Hamdani; Arifuddin Uksan; Parluhutan Sagala; Irwan Triadi (Jurnal Penelitian Hukum De Jure, 2026)
This article explores the inherent constitutional tensions within Article 12 of the 1945 Constitution of the Republic of Indonesia, which grants the President the authority to declare a state of danger. The primary problem identified in this study centers on the operational paradox of Article 12 through an outdated regulation, namely Law Number 23 of 1959 concerning the State of Danger. The crucial issues of this regulation include the granting of a 'blank check' (blanco mandaat) to the President without clear time limits, the absence of legislative (DPR) and judicial oversight, and its excessively militaristic nature, which renders it incapable of responding to modern crises such as health pandemics or cyber-attacks. Utilizing the analytical framework of the intellectual debate between Carl Schmitt and Hans Kelsen, this research dissects whether Indonesia currently leans toward an absolute decisionist sovereignty model or a controlled normativism model. A crucial issue is identified in the existence of Law Number 23 of 1959 concerning the State of Danger, which is deemed outdated, militaristic, and lacking in oversight, thereby potentially creating "legal black holes". Through a normative legal research method employing statutory, conceptual, and comparative approaches, this article outlines the urgency of reforming emergency constitutional law by reconceptualizing legislative and judicial oversight and adopting the proportionality test. The author argues that without structural reforms to the operational regulations of Article 12, the risk of a transition toward "autocratic legalism" will remain a latent threat to Indonesian democracy. This research finds that emergency law in Indonesia is currently in a perilous condition because it still relies on an outdated regulation (Law No. 23 of 1959). This legacy law grants a "blank check" (blanco mandaat) to the President, lacks a clear time limit, and shuts the door on parliamentary (DPR) and judicial oversight. Furthermore, the law is excessively militaristic and incapable of responding to modern crises such as health pandemics or cyber-attacks. As a concrete solution, this study proposes a new framework, the Pragmatic Hybrid Model. This model provides a middle ground, enabling the government to act swiftly during crises without devolving into a dictatorship.